Learning Activities, Exploration, and the Performance of Strategic Initiatives. (March 2016) - Walter, Jorge; Lechner, Christoph; Kellermanns, Franz W.
This study examines the contingent effect of the degree of exploration characterizing strategic initiatives on the relationship between group-level organizational learning activities (i.e., searching, processing, codifying, and practicing) and the performance of strategic initiatives. Results from a sample of 96 strategic initiatives conducted by three large European insurance corporations provide broad, albeit not unanimous, support for our prediction that the four learning activities are more beneficial when the degree of exploration is high. Moreover, for initiatives with lower degrees of exploration, we found no significant association of searching, processing, codifying, or practicing with initiative performance. These findings suggest that effective organizational learning depends not only on investments in learning activities, but also on the alignment between these investments and the degree of exploration inherent in the learning task.